The applicability of the Tanaka and Johnston analysis in a contemporary Western Australian population - Abaid Sidra; Zafar Sobia; Kruger Estie; Tennant Marc (Sciendo, 2022)
The Tanaka and Johnston mixed dentition analysis is a widely used method to predict the size of unerupted permanent canines and premolars. The aim of the present study was to determine the applicability of the Tanaka and Johnston analysis to Western Australian adolescents and develop a new regression equation.